EFEKTIVITAS PROGRAM SEKOLAH LAPANG PENGELOLAAN TANAMAN TERPADU (SL-PTT) TERHADAP PENDAPATAN PETANI PADI - Laili Furaidah; Lenny Widjayanthi; Julian Adam Rijal (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2016)
Integrated Crop Management Field School (FFS-ICM) or (SL-PTT) for food commodities is one of the government's efforts to increase productivity and income of a rice. By holding SL-PTT activities since 2008 until 2014 in the village of Kedaleman, the government expected that the productivity and income of rice farmers can be increased The study was conducted in the Kedaleman Village intentionally (purposive method).This study also used a descriptive analysis, scoring analysis, and income analysis.The results showed that: (1) the effective implementation of Integrated Crop Management Field School (FFS-ICM) in the Kedaleman village is effective, because as much as 45 or 100% of respondents were able to implement the components of Integrated Crop Management (ICM) ; (2) the level of motivation of rice farmers in participating in the implementation of Integrated Crop Management Field School (SL-PTT) is high; (3) the income of rice farmers who follow the program of Integrated Crop Management Field School SL-PTT is beneficial to the income of farmers in the amount of Rp 14,842,941.18 / MT / ha or USD 18,631,950.01 0.91 / MT / ha